(untitled) (Research, Society and Development, 2021)
We live in times where it is necessary to deconstruct some pedagogical resistances. Adapting towards the new virtual fronts, which has reconfigured the world in a globalized perspective of changing customs and values, leads to an effort to build bridges between school knowledge and expanded knowledge, being necessary to review some proposals that sustain teaching and learning, finding together with the subjects the real meaning of knowledge. The text’s comprehension is not only the result of a compendium of terms that are presented, but it gathers a large number of materialized elements in the virtual or printed interfaces. The formation of a multiple alphabetic amalgam (letters, words, phrases) and semiotic (images and children) signs to express an intended message, made digital language a communication model that transcends words, bringing changes in the form of understanding textual and thinking interface of the subject that contemplates it. The hyperlinks located in the hypertexts offers seductive enlargements to the user, while hiding virtual traps, so it needs to be foreseen by the teacher, in the elaboration of his activity, with orientations that are full of intentions, leading the student to avoid some of those shortcuts.